1986
DOI: 10.1002/j.1460-2075.1986.tb04243.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of synaptophysin, a major calcium-binding protein of the synaptic vesicle membrane.

Abstract: Synaptophysin, a mol. wt 38 000 glycopolypeptide of the synaptic vesicle membrane, was solubilized using Triton X‐100 and purified by immunoaffinity or ion‐exchange chromatography. From gel permeation and sucrose‐density centrifugation in H2O/D2O, a Stokes radius of 7.3 nm, a partial specific volume of 0.830 and a total mol. wt of 119 000 were calculated for the native protein. Cross‐linking of synaptic vesicles with glutaraldehyde, dimethylsuberimidate, or Cu2+ ‐o‐phenantroline, resulted in the formation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
147
1
6

Year Published

1988
1988
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(166 citation statements)
references
References 30 publications
12
147
1
6
Order By: Relevance
“…Synaptophysin and synaptoporin are two isoforms of a ubiquitous protein, present in all brain areas and co-localizing on synaptic vesicles (Fykse et al, 1993). Synaptophysin was found to bind Ca 2 ÷ (Rehm et al, 1986) and to form pores in lipid bilayers as a multimeric structure comparable to the formation of gap junctions by the related protein connexin (see Thomas et al, 1988;). It has been suggested that synaptophysin is able to form the actual fusionpore, probably in concert with a plasma membrane counterpart physophilin as a docking protein or receptor (Thomas and Betz, 1990).…”
Section: Complexesmentioning
confidence: 99%
“…Synaptophysin and synaptoporin are two isoforms of a ubiquitous protein, present in all brain areas and co-localizing on synaptic vesicles (Fykse et al, 1993). Synaptophysin was found to bind Ca 2 ÷ (Rehm et al, 1986) and to form pores in lipid bilayers as a multimeric structure comparable to the formation of gap junctions by the related protein connexin (see Thomas et al, 1988;). It has been suggested that synaptophysin is able to form the actual fusionpore, probably in concert with a plasma membrane counterpart physophilin as a docking protein or receptor (Thomas and Betz, 1990).…”
Section: Complexesmentioning
confidence: 99%
“…p38/synaptophysin is a membrane protein present in clear (synaptic) vesicles of neurons and endocrine cells [1][2][3][4]. From the amino acid sequence deduced from cDNAs encoding p38/synaptophysin, a model with several membrane spanning polypeptide segments and a carboxy-terminal protein domain exposed to the cytoplasmic surface has been constructed [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested to form a transmembrane channel for ions, or to interact with cytoplasmic factors via its cytoplasmic domain [7]. Since synaptophysin binds Ca 2+, it may also play a role in the release of neurotransmitters stored in clear (synaptic) vesicles [3].…”
Section: Introductionmentioning
confidence: 99%
“…Keywords: depression; psychopharmacology; psychosis; SSRI; synapsin; synaptophysin INTRODUCTION Synaptic vesicle proteins (SVP) such as synapsin I-III, synaptophysin, synaptotagmin, and synaptobrevin (VAMP -vesicle-associated membrane protein) play a critical role in synaptic plasticity, and are required for vesicle fusion and neurotransmitter release. [1][2][3][4][5][6] Hence, changes in the expression of these proteins may contribute to the molecular effects of antidepressant treatment and associated behavioral and cognitive alterations. Previous studies have shown that antidepressants modulate de novo gene transcription and synthesis of proteins involved in neural and synaptic plasticity; in a recent transcriptomic study, a decreased expression of VAMP was found with imipramine and sertraline.…”
mentioning
confidence: 99%